Public Perceptions, Factors, and Incentives Influencing Patient Willingness to Share Clinical Images for Artificial Intelligence-Based Healthcare Tools. - Ly, Sophia.; Reyes-Hadsall, Sophia.; Drake, Lara.; Zhou, Guohai.; Nelson, Caroline.; Barbieri, John S; Mostaghimi, Arash. (Tufts University. Tisch Library., 2023)
Keywords: Artificial intelligence, General dermatology, Survey, Clinical research.; Springer Open.